Penilaian Mutu Perguruan Tinggi Dengan Perspektif Balance Scorecard di IAIN Syaikh Abdurahman Siddik Bangka Belitung - Marheni Marheni (Sustainable, 2019)
The purpose of this study is to assess the quality of tertiary institutions from four perspectives, namely financial perspective, customer perspective, internal business process perspective, learning and growth perspective for IAIN Sheikh Abdurahman Siddik Bangka Belitung. Based on the discussion and analysis of the data it can be concluded that 1) based on a financial perspective shows that the growth of assets and leverage shows that there is a tendency for growth; 2) Based on the measurement of the Growth and Learning perspective (Learning and Growth) explained that workers, lecturers and employees have felt the management system at the university is good; 3) Based on the measurement of the Internal Business (Internal Business Process), universities make efforts to improve the quality of students; 4) Based on the perspective of the customer (Customer) the results show that students feel the service provided is good. ABSTRAK Tujuan penelitian ini adalah menilai mutu perguruan tinggi dilihat dari empat perspektif yaitu perspektif keuangan, perspektif pelanggan, perspektif proses bisnis internal, perspektif pembelajaran dan pertumbuhan bagi IAIN Syaikh Abdurahman Siddik Bangka Belitung. Berdasarkan pembahasan dan analisis data disimpulkan bahwa 1) berdasarkan perspektif keuangan menunjukkan bahwa pertumbuhan aset dan leverage menunjukkan adanya perkembangan yang cenderung meningkat; 2) Berdasarkan pengukuran perspektif Pertumbuhan dan Pembelajaran (Learning and Growth) dijelaskan bahwa pekerja, dosen dan karyawan sudah merasakan sistem pengelolaan di universitas sudah baik; 3) Berdasarkan pengukuran Bisnis Internal (Internal Bussiness Process), perguruan tinggi melakukan upaya untuk meningkatkan mutu mahasiwa; 4) Berdasarkan perspektif Pelanggan (Customer) berupa hasilnya menunjukkan bahwa mahasiswa merasakan pelayanan yang diberikan baik.